A dissertation Submitted to the Department of English Language in Partial Fulfilment of the Requirements of Master’s Degree in Didactics of EFL - Somia REMADNIA (My University, 2023)
Abstract The aim of this study is to investigate the impact of using the British Council Platform on enhancing the listening skills of first year Bachelor English Language students at Mohamed Cherif Messaadia University, in Souk-Ahras. To test the main hypothesis that suggests the possibility of improving the listening skills through the use of the British Council Platform a pre-test and post-test intruments were conducted during their oral course, and to confirm the findings of the experiment an interview was held to Oral comprehension teachers, to know their perceptions on the use of the British Council Platform in enhancing listening skills. The data gathered proves that the British Council Platform is truly effective in enhancing the listening skills. Thus, the researcher’s main hypothesis is truly confirmed. Moreover, it recommended the British Council Platform as a material through which teachers can decrease the listening difficulties that students may encounter. Finally, convince teachers to adapt and make use of the British Council Platform during their oral classes --------------------------- الملخص الهدف من هذه الدراسة هو التحقيق في تأثير استخدام منصة المجلس الثقافي البريطاني في تعزيز مهارة الاستماع لطلاب السنة الأولى بكالوريوس اللغة الإنجليزية في جامعة محمد شريف مساعدية، في سوق أهراس. لاختبار الفرضية الرئيسية التي تشير إلى إمكانية تحسين مهارة الاستماع من خلال استخدام منصة المجلس الثقافي البريطاني، تم إجراء اختبار ما قبل وبعد التجربة خلال الفصول الشفوية، ولتأكيد نتائجها، تم إجراء مقابلة لمعلمي الفهم الشفهي، لمعرفة تصوراتهم حول استخدام منصة المجلس الثقافي البريطاني في تعزيز مهارات الاستماع. تثبت البيانات التي تم جمعها أن منصة المجلس الثقافي البريطاني فعالة حقًا في تعزيز مهارة الاستماع. وبالتالي، تم تأكيد الفرضية الرئيسية للباحث حقًا. علاوة على ذلك، أوصت الدراسة بمنصة المجلس الثقافي البريطاني كأداة يمكن للمدرسين من خلالها تقليل صعوبات الاستماع التي قد يواجهها الطلاب. أخيرًا، اقنعت المعلمين بالتكيف والاستفادة من منصة المجلس الثقافي البريطاني خلال الفصول الشفوية ------------------------- Résumé Le but de cette recherche est d'étudier l'impact de l'utilisation de la plateforme du British Council pour améliorer les compétences d'écoute des étudiants de première année de licence en langue anglaise à l'Université Mohamed Cherif Messaadia, à Souk-Ahras. Pour tester l'hypothèse principale qui suggère la possibilité d'améliorer les compétences d'écoute grâce à l'utilisation de la plate-forme du British Council, des instruments de pré-test et de post-test ont été menés pendant leur cours oral, et pour confirmer les résultats de l'expérience, un entretien a été organisé. Aux enseignants de compréhension orale, pour connaître leurs perceptions sur l'utilisation de la plate-forme du British Council dans l'amélioration des compétences d'écoute. Les données recueillies prouvent que la plateforme du British Council est vraiment efficace pour améliorer l'écoute. Ainsi, l'hypothèse principale du chercheur est véritablement confirmée. De plus, il a recommandé la plate-forme du British Council comme matériel grâce auquel les enseignants peuvent réduire les difficultés d'écoute que les élèves peuvent rencontrer. Enfin, convaincre les enseignants d'adapter et d'utiliser la plateforme du British Council lors de leurs cours oraux